2012
DOI: 10.1007/s11357-012-9474-y
|View full text |Cite
|
Sign up to set email alerts
|

SIRT1 inhibits apoptosis of degenerative human disc nucleus pulposus cells through activation of Akt pathway

Abstract: Many studies have demonstrated that SIRT1, an NAD(+)-dependent deacetylase, reduces apoptosis in several different cells. However, the role of SIRT1 in apoptosis of disc nucleus pulposus (NP) cells remains unclear. The present study was performed to determine whether degenerative human NP would express SIRT1, and to investigate the role of SIRT1 in NP cells apoptosis. The expression of SIRT1 in disc NP of patients (>55 years) with lumbar disc degenerative disease (DDD) and the disc NP of patients (<25 years) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
47
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 43 publications
8
47
0
Order By: Relevance
“…The expression of Coll2α1 and aggrecan increased significantly, illustrating that the intervertebral disc degeneration occurrence and development were reversed. These results were similar to those obtained by others (Gagarina et al, 2010;Wang et al, 2012).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The expression of Coll2α1 and aggrecan increased significantly, illustrating that the intervertebral disc degeneration occurrence and development were reversed. These results were similar to those obtained by others (Gagarina et al, 2010;Wang et al, 2012).…”
Section: Discussionsupporting
confidence: 93%
“…Current studies show that there is a close relationship between the intervertebral disc diseases and matrix metabolism imbalance (Matrisian, 1990;Boileau et al, 2011;Chen et al, 2011). Silence mating type information regulation 2 homolog 1 (SIRT1), by inhibiting the expression of matrix metalloproteinase-1 (MMP-1), promotes cartilage extracellular matrix synthesis (Wang et al, 2012). In this study, we detected the expression of SIRT1 and MMP-1 in degenerative human nucleus pulposus intervertebral disc specimens and analyzed the functions of SIRT1 and MMP-1 in the development of intervertebral disc degeneration, in order to find a novel target for the therapy of intervertebral disc degenerative diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we identified FOXO3 as a novel mediator of NP cell adaptation to hypoxia and demonstrated that FOXO3 and, to a lesser extent, FOXO1 regulate the expression of autophagy genes and activation in NP cells. Although a causal relationship between autophagy defects and IDD has not yet been established, our findings showed that FOXO function promotes NP cell survival under oxidative and inflammatory stresses, major drivers of NP cell apoptosis and aging‐related IDD (Nasto et al, 2013; Wang et al, 2013; Yang et al, 2014), and thus suggest that activation of FOXO in aged IVD could increase autophagy and protect NP cells from stress‐induced apoptosis. Further supporting this hypothesis, various studies have shown that autophagy activation can protect NP cells against different apoptotic insults (Jiang, Jin, Wang, Jiang, & Dong, 2014; Jiang, Zhang, et al, 2014).…”
Section: Discussionmentioning
confidence: 55%
“…Correspondingly, additional in vivo studies (14) demonstrated that Sirt1 exerts an anti-inflammatory effect in cartilage during OA. Moreover, mechanistic studies have provided further support that SIRT1 promotes chondrocyte survival through various pathways (15)(16)(17)(18)(19)-in particular, deacetylation of p65/ RelA-which reduces iNOS gene expression after IL-1b challenge of chondrocytes (20). Despite the wealth of information regarding the beneficial effects exerted by SIRT1 in maintaining chondrocyte survival and attenuating inflammation, very little is known about the impact of SIRT1 on cartilage destruction during OA.…”
mentioning
confidence: 99%